2016
DOI: 10.4314/ejhs.v26i5.6
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of health centers and primary hospitals for the implementation of proposed health insurance schemes in Southwest Ethiopia

Abstract: BACKGROUND: In response to the 2005 World Health Assembly, many low income countries developed different healthcare financing mechanisms with risk pooling stategy to ensure universal coverage of health services. Accordingly, service availability and readiness of the health system to bear the responsibility of providing service have critical importance. The objective of this study was to assess service availability and readiness of health centers and primary hospitals to bear the responsibility of providing ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…This impairs the ability to implement referral systems between health care facilities and providers. A study done in Ethiopia showed that, 38.1% of studied primary health care facilities had no fixed or mobile telephone services [39,40]. To improve communication in these settings there is a need for public private partnership to allow the private sector to help in the installation of telecommunication systems in the health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This impairs the ability to implement referral systems between health care facilities and providers. A study done in Ethiopia showed that, 38.1% of studied primary health care facilities had no fixed or mobile telephone services [39,40]. To improve communication in these settings there is a need for public private partnership to allow the private sector to help in the installation of telecommunication systems in the health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…This impairs the ability to implement referral systems between health care facilities and providers. A study done in Ethiopia showed that, 38.1% of studied primary health care facilities had no fixed or mobile telephone services [40,41]. To improve communication in these settings there is a need for public private partnership to allow the private sector to help in the installation of telecommunication systems in the health facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Service hour and efficiency of CBHI service were found to be positively associated with satisfaction of CBHI scheme [57], work load without additional incentives negatively affects CBHI utilization [19]. Most of the health institutions were not ready to CBHI scheme's requirements/criteria [58]. Inadequacy of health sector in terms of quality, organized working practice, resources and premises; forcing members to search for expensive private sectors [54].…”
Section: Factor Analysismentioning
confidence: 99%